Halal Industry Development Strategies Based on Small and Medium-Sized Enterprises for Rendang Entrepreneurs in Payakumbuh - Ajidin, Zilal Afwa; Gusmal; Ajidin, Asep (ITQAN: Journal of Islamic Economics, Management, and Finance, 2024)
West Sumatra has much potential for halal culinary development in Indonesia. One of the famous food products is rendang. According to CNN, this product has gone global and is the most delicious food globally. In the context of halal culinary tourism development, Payakumbuh is one of the cities that contributes to the development of halal culinary businesses, especially rendang. A rendang village in Payakumbuh is a collection of several Small and Medium Enterprises promoting rendang businesses. Rendang entrepreneurs in Payakumbuh also play a role in accelerating the halal industry in their area. Rendang sales can also be accepted by consumers and sent to several regions in Indonesia and even the world. It aligns with Law Number 33 of 2014 concerning Halal Product Guarantees. However, there are also many obstacles faced by rendang entrepreneurs in Payakumbuh in developing their businesses: limited capital, weak managerial skills, and marketing constraints. This research aims to discover rendang entrepreneurs' strategies to develop the halal industry. The method used is qualitative analysis. Next, the analysis technique used is SWOT analysis. Several steps can be taken to optimize rendang sales, including consumer awareness, halal services, digital marketing and supporting services. The government needs to support the development of the halal industry in Indonesia.